Karakterisasi Papan Partikel Dari Kulit Buah Kakao (Theobroma cacao L.) Dalam Variasi Jenis Dan Konsentrasi Perekat - Hugo, Harbert; Harsojuwono, Bambang Admadi; Suwariani , Ni Putu (Department of Agroindustrial Technology, Faculty of Agricultural Technology, Udayana University, 2025)
Particle board is an artificial board created by combining lignocellulosic chips/particles using pressed synthetic adhesive to obtain characteristics similar to solid wood. This research aims to determine the effect of the types and concentrations of adhesive that produces the best particle board characteristics. This research used a Randomized Block Design (RBD) with treatment variations between types of adhesive, namely PVAc, epoxy, and urea formaldehyde, as well as adhesive concentration levels consisting of 50%, 55%, 60%, and 65%, with a total of 12 combinations. Each treatment was grouped into 2 based on the time the particle board was made to obtain 24 experimental units. The variables observed were physical properties which included: density, water content, water absorption capacity, and thickness expansion, then mechanical properties which included: modulus of elasticity, modulus of rupture, internal bonding, and screw holding strength. The data obtained was analyzed for diversity and continued with the Honestly Significant Difference Test (HSD). The research results showed that the types and concentrations of adhesive had a very significant effect on water absorption capacity, thickness expansion, MOR, MOE, internal bonding, screw holding strength, had a significant effect on water content, and had no significant effect on density. Applying a 65% concentration of PVAc adhesive results in properties that fulfill most of the test criteria outlined in SNI 03-2105-2006 regarding particle boards, with a density value of 0.83 g/cm3, water content 12.81%, water absorption capacity 10.97%, thickness expansion 1.25%, MOR 33.38 kg/cm2, MOE 1490.83 kg/cm2, internal bonding 4.68 kg/cm2, and screw holding strength 4.85 kgf.